2003
DOI: 10.1007/s00068-003-1277-5
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Kampala Trauma Score (KTS) with the Revised Trauma Score (RTS), Injury Severity Score (ISS) and the TRISS Method in a Ugandan Trauma Registry

Abstract: Background:The public health significance of injuries that occur in developing countries is now recognized. In 1996, as part of the injury surveillance registry in Kampala, Uganda, a new score, the Kampala Trauma Score (KTS) was instituted. The KTS, developed in light of the limited resource base of sub-Saharan Africa, is a simplified composite of the Revised Trauma Score (RTS) and the Injury Severity Score (ISS) and closely resembles the Trauma Score and Injury Severity Score (TRISS). Patients and Methods:The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
75
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 70 publications
(79 citation statements)
references
References 18 publications
3
75
1
Order By: Relevance
“…When stratifying MGAP scores as low (23)(24)(25)(26)(27)(28)(29), intermediate (18)(19)(20)(21)(22) and high (3-17) risk for death, the in-hospital mortality rates were uniformly higher than in the original validation cohort of the MGAP score in France (Table 3). The area under the ROC curve for the MGAP score in the French validation cohort was 0.90, compared with 0.85 in the subset of patients with sufficient data to Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When stratifying MGAP scores as low (23)(24)(25)(26)(27)(28)(29), intermediate (18)(19)(20)(21)(22) and high (3-17) risk for death, the in-hospital mortality rates were uniformly higher than in the original validation cohort of the MGAP score in France (Table 3). The area under the ROC curve for the MGAP score in the French validation cohort was 0.90, compared with 0.85 in the subset of patients with sufficient data to Fig.…”
Section: Resultsmentioning
confidence: 99%
“…MGAP values ranged from 10 to 29, with a median value of 23 . GAP values ranged from 6 to 24, with a median value of 19 (IQR [14][15][16][17][18][19][20][21][22].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This study reinforces their findings in a larger patient cohort of 2,855 patients, as the logistic regression model for mortality showed KTS to be a predictor of mortality, with adequate fit based on evaluation of goodness-of-fit using Akaike Information Criteria and Pearson's v 2 test. Furthermore, using the definition of severe injury employed by MacLeod et al [18], the Yaoundé study population yielded a sample of 244 patients to which to apply this methodology for subgroup analysis. Again, this study's findings confirm the performance of KTS as a scoring system for this subset of patients in a larger sample and a different study context, suggesting greater generalizability of KTS than the initial studies may have indicated.…”
Section: Discussionmentioning
confidence: 99%
“…Whereas efforts have been made to introduce paediatric triage in Uganda such as Emergency Triage Assessment and Treatment Plus (ETAT+), the WHO tool and Integrated Management of Childhood Illness (IMCI) 9 , such programs are lacking for adult emergency medical care and it is not clear if hospitals have local protocols for adult triage. One triage score, the Kampala Trauma Score (KTS), was initially found to be a trauma triage tool for resource poor settings 10 . However, its usefulness was found to be limited 11 .…”
Section: Introductionmentioning
confidence: 99%